Boycott Calls, Brand Image on Loyalty and Purchasing Decisions of Israel-Affiliated Products - Jaya, Athira Dwi; Romadhoni, Buyung; Muchran, Muchriady (International Journal of Education, Management, and Technology, 2025)
This study aims to analyze the impact of boycott calls on consumer loyalty and purchase decisions for products affiliated with Israel, as well as the role of brand image in these relationships. The study employs a mixed-methods approach, utilizing quantitative data collected through questionnaires and qualitative data through interviews. The findings indicate that boycott calls have a positive influence on consumer loyalty and purchase decisions, suggesting that some consumers remain loyal and continue to purchase despite the boycott pressure. Additionally, brand image was found to have a negative impact on consumer loyalty, though loyalty remains stable despite the boycott pressure. Consumer loyalty also serves as a mediator, influencing purchase decisions even in the presence of boycott calls. This study provides insights into the complex dynamics between boycott calls, brand image, loyalty, and purchasing decisions within the context of sensitive social and political issues.